Description of a new species of Characidium Reinhardt, 1867 (Characiformes: Crenuchidae) from the Chapada Diamantina, Bahia, and redescription of Characidium bimaculatum Fowler, 1941 - Melo, Marcelo R. S.; Espíndola, Vinicius C. (Zootaxa, 2016)
A new species of Characidium Reinhardt, 1867 endemic to tributaries of the upper rio Paraguaçu in the Chapada Diamantina, Bahia, Brazil, is described. The new species can be distinguished from its congeners except C. bahiense, C. bimaculatum, C. laterale, C. nana, C. nupelia, and C. xavante, by having a conspicuous peduncular blotch in addition to the basicaudal spot on the base of the middle caudal-fin rays. Among other features, the new species differs from C. bahiense, C. laterale, C. nana, C. nupelia, and C. xavante by having a complete lateral line with 32–36 perforated scales (vs. lateral line short, with 9–11 perforated scales), and from C. bimaculatum by the body pigmentation pattern, with secondary bars present (vs. absent), total bars 11–16 (vs. 10–12), peduncular blotch rounded (vs. horizontally elongated), and mature males not having a darker dorsal fin (vs. proximal third of dorsal fin darker in mature males). Characidium bimaculatum, a poorly known species from Northeastern Brazil, is redescribed.